Density Functional Calculations on a Double Hydrogen Bonded Dimer of 1-(2-Furylmethylene)-4-phenyl Thiosemicarbazide - Wang, H.Y.; Zhao, P.S.; Shao, D.L.; Li, R.Q.; Song, J.; Jian, F.F. (Asian Journal of Chemistry, 2010)
Density functional theory (DFT) calculations on a double hydrogenbonded dimer of 1-(2-furylmethylene)-4-phenyl thiosemicarbazide were carried out at B3LYP/6-311G** level. The optimized geometry of the dimer closely resembles that in the crystal. The calculated results show that the total energy of the dimer is much lower than the sum of energies of the two monomers and the average strength of the double hydrogen bond is about 21.660 kJ/mol. In order to probe the origin of the interactions in the dimer, natural bond orbital (NBO) analyses have been performed. The thermodynamic properties of the title compound at different temperatures have also been calculated on the basis of vibrational analyses and the change of Gibbs free energy for dimerization of the two monomers ΔGT = -17.365 kJ/mol at 298.15 K and 0.1 MPa, which implies the spontaneous process of the dimer formation.